COMPOUND DEPRESSED SKULL FRACTURE, ITS ASSOCIATION WITH INFECTION AND IMPORTANCE OF THE TIME FROM THE ACCIDENT - Rasheed, Handren Muhamad; Faraj, Pakhshan Mohammed (Journal of Sulaimani Medical College, 2022)
Background Infection can occur after compound depressed skull fracture (DSF) if not timely treated. Objectives To assess the time effect from accident to surgical intervention on surgical site infection (SSI). Patients and Methods A retrospective cohort study was performed on 63 patients admitted to Shar Hospital from September 1, 2020, to May 13, 2021. Demographic features, type of trauma, time from accident to intervention, Glasgow Coma Scale (GCS), DSF location, associated brain injuries, dural tear, and admission to intensive trauma care unit (ITCU) were recorded. Patients followed up for 30 days. Results Mean±SD (standard deviation) of ages was 23.8±18.1 years, ranging from 1-70. The male-to-female ratio was (4.25:1), and patient majorities (46% and 87.3%) were workers outside the city, respectively. Patients’ ages, occupations, and residencies were significantly associated with SSI; p-values of <0.001, <0.001, and 0.004, respectively. 4.8% of patients were afflicted with SSI. Associations of admission GCS and DSF location with SSI were significant. Surgery was done for most patients (52.4%) within six hours, but the association of time from accident to surgery was non-significant. Mean±SD duration from accident to surgery was 8.1±5.1 hours, ranging from 1.5-29. All afflicted patients with SSI had basal skull fracture (BSF) and aerocele. The dural tear did not associate with SSI. All afflicted patients who underwent frontal sinus cranialization were admitted to the ITCU and significantly associated with SSI. Conclusion There was no significant association between SSI occurrence and the time from the accident until surgical intervention.
Keywords: Depressed skull fracture (DSF); Head injury; Head trauma; Infection; Surgical site infection (SSI)